OPERASIONAL KOPERASI ISHLAH DAYAH MALIKUSSALEH PANTON LABU MENURUT PERSPEKTIF AKAD TABARRU’PADA ASURANSI SYARIAH - Hidayatina Hidayatina; Muhammad Umar Joni (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2018)
Koperasi Ishlayah Dayah Malikussaleh Panton Labu is a form of business cooperative. However, operationally it is different from Islamic cooperatives in general. The formulation of the problem is: 1) How is the operation of the Ishlah cooperative in the Dayah Malikussaleh Panton Labu? 2) How is the operation of the Ishlah cooperative in the Dayah Malikussaleh Panton Labu according to the tabarru contract 'perspective on Islamic insurance? While the method used is field research using qualitative research with the help of qualitative data. The results of this study are: 1) the operation of the Ishlah cooperative is divided into 3: a) the existence of principal savings, mandatory savings and voluntary savings collected from each member of the cooperative. b) cooperative funds are managed in the form of kiosks, mini markets and the existence of oil palm plantations owned by cooperatives that are c) The remaining proceeds of the Ishlah cooperative are not shared with cooperative members, but cooperative business development is used, to cover the salary shortages of teachers and employees of Dayah Malikussaleh and for the construction and renovation of the dayah malikussaleh infrastructure. 2) tabarru 'which is in sharia insurance, where the remaining results of the business are not shared with members of the cooperative, but will be used as funds to help fellow members of the cooperative, such as to cover the salary shortages of teachers and employees of dayah Malikussaleh. However, cooperative funds are directly managed by the Ishah cooperative. Unlike the case with tabarru 'funds on insurance that invests in sharia financial institutions, and the profits derived from these investments will be included in the tabarru account.